Lymphoid aggregates in the bone marrow biopsies of patients with myelodysplastic syndromes – A potential prognostic marker? - Book, Reut; Ben-Ezra, Jonathan; Glait Santar, Chen; Kay, Sigi; Stemer, Galia; Oster, Howard S.; Mittelman, Moshe (Frontiers in Oncology, 2023)
Background: Lymphoid aggregates (LA) are occasionally seen in bone marrow biopsies (BMB) of myelodysplastic syndromes (MDS) patients. Our aim was to evaluate their incidence and association with prognosis. Methods: We compared BMB reports of MDS patients treated at the Tel Aviv Sourasky Medical Center (2011-2018), and controls (2015-2017, normal BMB), and examined the charts of the MDS patients (LA+ and LA-). Categorical, normally and non-normally distributed continuous variables were compared using Fisher's exact, independent t and Mann-Whitney tests respectively. Adjusted (age, gender, lymphocytes, white blood cells (WBC) and diabetes mellitus (DM)) Cox proportional hazard model examined survival at 12 and 24 months. Results: MDS patients (N=140) were older than controls (N=38; 74.1 vs 69.2 years, p=0.005); 34 MDS (24.3%) and 5 controls (13.2%) had LA+ (P=0.141). CD20/CD3 staining suggested LA polyclonality. MDS/LA+ (vs MDS/LA-) patients were younger, with a trend (not statistically significant) towards poor prognostic parameters: lower Hb, WBC, and platelets, higher LDH, BM cellularity, and IPSS-R score. The incidence of cardiovascular disease was similar, but MDS/LA+ had twice the incidence of DM (38.2% vs 19.0%, p=0.022). Similar trend for cancer (26.5% vs 14.3%, p=0.102). Twelve-month survival: 24/34 (70.6%) MDS/LA+; 88/106 (83.0%) MDS/LA- (p=0.140). This trend, seen in Kaplan-Meier curves, disappeared at 24 months. The hazard ratio for LA was 2.283 (p=0.055) for 12 months. Conclusion: These preliminary data suggest LA are relatively common (24%) in MDS BMB, and might indicate poor prognosis. This may reflect involvement of the immune system in MDS. Future studies will examine larger groups, to clarify the incidence, significance and the pathophysiology.